Analisis Faktor Faktor yang Mempengaruhi Financial Literacy di Kalangan Mahasiswa Universitas Muhammadiyah Riau Pekanbaru - Mimelientesa Irman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Financial literacy is a basic need for everyone to avoid financial problems. This study aims to find out how the level of financial literacy students of Muhammadiyah University of Riau Pekanbaru. This research concerned were knowledge of personal finance, savings and loans, insurance and investment. Respondents in this study were 91 active students at Muhammadiyah University of Riau. The method used in this research is descriptive method and binary logistic test. The results showed that the students financial literacy influenced by GPA of students, while gender and work experience have no significant influence on student's financial literacy. Keywords: Financial Literacy, Gender, GPA, Work Experience